Ethyl pyruvate inhibits glioblastoma cells migration and invasion through modulation of NF-κB and ERK-mediated EMT - Huang, Qing; Fu, Yongming; Zhang, Shan; Zhang, Youxiang; Chen, Simin; Zhang, Zuping (PeerJ, 2020)
Background Glioblastoma is a grade IV glioma with the highest degree of malignancy and extremely high incidence. Because of the poor therapeutic effect of surgery and radiochemotherapy, glioblastoma has a high recurrence rate and lethality, and is one of the most challenging tumors in the field of oncology. Ethyl pyruvate (EP), a stable lipophilic pyruvic acid derivative, has anti-inflammatory, antioxidant, immunomodulatory and other cellular protective effects. It has been reported that EP has potent anti-tumor effects on many types of tumors, including pancreatic cancer, prostate cancer, liver cancer, gastric cancer. However, whether EP has anti-tumor effect on glioblastoma or not is still unclear. Methods Glioblastoma U87 and U251 cells were treated with different concentrations of EP for 24 h or 48 h. CCK8 assay and Colony-Formation assay were performed to test the viability and proliferation. Wound-healing assay and Transwell assay were carried out to measure cell invasion and migration. Western blot was not only used to detect the protein expression of epithelial-mesenchymal transition (EMT)-related molecules, but also to detect the expression and activation levels of NF-κB (p65) and Extracellular Signal Regulated Kinase (ERK). Results In glioblastoma U87 and U251 cells treated with EP, the viability, proliferation, migration, invasion abilities were inhibited in a dose-dependent manner. EP inhibited EMT and the activation of NF-κB (p65) and ERK. With NF-κB (p65) and ERK activated, EMT, migration and invasion of U87 and U251 cells were promoted. However the activation of NF-κB (p65) and ERK were decreased, EMT, migration and invasion abilities were inhibited in U87 and U251 cells treated with EP. Conclusion EP inhibits glioblastoma cells migration and invasion by blocking NF-κB and ERK-mediated EMT.
Keywords: Ethyl pyruvate; Migration; Invasion; EMT (epithelial–mesenchymal transition); NF-κB; ERK; Glioblastoma